1998
DOI: 10.1063/1.121250
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-wave operation of InGaN/GaN/AlGaN-based laser diodes grown on GaN substrates

Abstract: InGaN multi-quantum-well-structure laser diodes (LDs) grown on GaN substrates were demonstrated. The LDs showed a small thermal resistance of 30 °C/W and a lifetime longer than 780 h despite a large threshold current density of 7 kA/cm2. In contrast, the LDs grown on a sapphire substrate exhibited a high thermal resistance of 60 °C/W and a short lifetime of 200 h under room-temperature continuous-wave operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
287
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 500 publications
(294 citation statements)
references
References 10 publications
6
287
0
1
Order By: Relevance
“…These DDs are consistent with the values given for GaN epitaxial films in the literature. 3,4,9 Analysis of the forward bias I-V data indicated that the predominant current mechanism of the Al 0.22 Ga 0.78 N / AlN/ GaN heterostructure with high DDs in the intermediate bias voltage region that was investigated in this study was a dislocation-governed current-transport mechanism rather than the other currenttransport mechanisms.…”
Section: ͑12͒mentioning
confidence: 99%
See 1 more Smart Citation
“…These DDs are consistent with the values given for GaN epitaxial films in the literature. 3,4,9 Analysis of the forward bias I-V data indicated that the predominant current mechanism of the Al 0.22 Ga 0.78 N / AlN/ GaN heterostructure with high DDs in the intermediate bias voltage region that was investigated in this study was a dislocation-governed current-transport mechanism rather than the other currenttransport mechanisms.…”
Section: ͑12͒mentioning
confidence: 99%
“…[1][2][3] Because of the large energy band gap, the applications of Al x Ga 1−x N are extensive, such as for visible-blind ultraviolet ͑UV͒ detectors, laser diodes, and short-wave light-emitting diodes. 4 High-quality AlGaN/GaN heterostructures have been shown to contain twodimensional electron gas ͑2DEG͒, which has attracted special interest due to its potential applications in high mobility transistors operating at high power and high temperature levels. 5,6 The device structures are usually grown on highly lattice-mismatched substrates, such as sapphire, 7 SiC, 8 or Si.…”
Section: Introductionmentioning
confidence: 99%
“…6,7) Few single-crystal GaN substrates have been fabricated until recently and, consequently, most GaN-based devices had been grown on heterogeneous substrates such as sapphire, SiC, or Si. [8][9][10][11][12] Additionally, the highpurity epitaxial layers of GaN that are needed for drift layers of vertical-type power devices are difficult to grow by conventional metal-organic chemical vapor deposition (MOCVD), because of the inevitable incorporation of carbon from metalorganic sources, 5,[13][14][15] despite the great success of MOCVD in the commercialization of optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of device quality GaN, InGaN and AlGaN over the past five years has lead to the commercialization of blue and green light emitting diodes, along with demonstrations of violet laser diodes and a variety of electronic devices [1] [2] [3] [4] [5] [6] [7] [8] [9] [10]. In addition, a number of photodetectors based on photoconductive and junction devices have also recently been reported [11] [12] [13].…”
Section: Introductionmentioning
confidence: 99%